Free Higher Education: On and Off the Agenda with the Political Tide - de Gayardon, Ariane (International Higher Education, 2021)
This article provides an update on the international free tuition movement as of 2020. Through the examples of the United States and New Zealand, it shows that free tuition is a highly politicized issue used by policy makers who need to gain power. The economic crisis stemming from the COVID-19 pandemic will, however, make such an expansive policy unviable in the short-term, but might be an opportunity for income-targeted free tuition to develop.